Bank stress testing: A stochastic simulation framework to assess banks' financial fragility - Giuseppe Montesi; Giovanni Papiro (Risks, 2018)
We present a stochastic simulation forecasting model for stress testing that is aimed at assessing banks' capital adequacy, financial fragility, and probability of default. The paper provides a theoretical presentation of the methodology and the essential features of the forecasting model on which it is based. Also, for illustrative purposes and to show in practical terms how to apply the methodology and the types of outcomes and analysis that can be obtained, we report the results of an empirical application of the methodology proposed to the Global Systemically Important Banks (G-SIB) banks. The results of the stress test exercise are compared with the results of the supervisory stress tests performed in 2014 by the Federal Reserve and EBA/ECB.
Keywords: C15; C63; G21; G28; G32; 330; capital adequacy; economic capital; financial fragility; liquidity risk; Monte Carlo simulation; probability of default; Solvency risk; SREP; stochastic simulation; stress testing